How motivated are patients with type 2 diabetes to change their lifestyle? A survey among patients and healthcare professionals. Issue 6 (December 2015) - Linmans, Joris J.; Knottnerus, J. André; Spigt, Mark
Highlights: We assessed the level of motivation to change lifestyle in patients with T2DM. Patients were not motivated to increase their lifestyle. Many patients had a deficient physical activity level. Patients and professionals have poor agreement for the patients' level of motivation to change. The motivation level should be assessed regularly in usual-care to optimize lifestyle management. Abstract: Aim: It is unknown to what extend patients with type 2 diabetes mellitus (T2DM) in primary care are motivated to change their lifestyle. We assessed the level of motivation to change lifestyle and the agreement for that level between patients and healthcare professionals. Methods: Patients with T2DM (150) filled in a questionnaire to assess the level of motivation to change their lifestyle, using a single question with three answer options. We investigated the agreement for this level between these patients and their healthcare professionals (12 professionals). In addition, we investigated and compared the level of physical activity as indicated by the patients and the healthcare professionals. Results: A large part of the patients reported to have a deficient physical activity level (35% according to patients, 47% according to healthcare professionals, kappa 0.32) and were not motivated to change their lifestyle level (29% according to patients, 43% according to healthcare professionals, kappa 0.13). Patients tended to overestimate their physical activity and their motivation to change in comparison with their healthcare professionals. Conclusions: Patients with T2DM in primary care should increase their physical activity level. Healthcare professionals often do not know whether patients are motivated to change their lifestyle, and should therefore assess motivation regularly to optimize lifestyle management.